Carbon dots: Applications in bioimaging and theranostics - Boakye-Yiadom, Kofi Oti; Kesse, Samuel; Opoku-Damoah, Yaw; Filli, Mensura Sied; Aquib, Md; Joelle, Mily Maviah Bazezy; Farooq, Muhammad Asim; Mavlyanova, Rukhshona; Raza, Faisal; Bavi, Rohit; Wang, Bo (International journal of pharmaceutics, 2019)
[Display omitted] Carbon dots are a carbonaceous nanomaterial that were discovered accidentally and are now drawing significant attention as a new quantum-sized fluorescent nanoparticle. Carbon dots are biocompatible, non-toxic, photostable, and easily functionalized with good photoluminescence and water solubility. Due to these unique properties, they are used broadly in live cell imaging, catalysis, electronics, biosensing, power, targeted drug delivery, and other biomedical applications. Here, we review the recent development of carbon dots in nanomedicine from their use in drug carriers to imaging agents to multifunctional theranostic systems. Finally, we discuss the challenges and views on next-generation carbon dot-based theranostics for clinical applications.